NUMERICAL STUDY ON CONDENSATION IN IMMERSED CONTAINMENT SYSTEM OF ADVANCED SMR DURING UNCONTROLLED DEPRESSURIZATION - Susyadi; Tjahjono, Hendro; Tjahyani, D.T. Sony (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2017)
A number of Small Modular Reactor designs have been developed by several countries and mostly each comes with specific innovative improvements. One of them is NuScale reactor which implements a steel, small size immersed-in-pool containment system. This new approach derives new challenges as the control for temperature and pressure inside the containment is conducted without any active system. Passive heat transfer and condensation is important parameter that needs to be investigated for this kind of containment design. Hence, this work examines the condensation, pressure and the effect of pool temperature on the capability of the containment to remove heat and maintain integrity passively. The work is performed using numerical simulation by modeling the reactor into RELAP5 code. The calculation result shows that during depressurization, the maximum pressure limit of 5.5 MPa is not exceeded. Besides, the containment design provides enough capability to transfer heat from the containment to the water pool passively. This work also investigates sensitivity analysis of pool temperature which shows that for the increase of about 17 oC, the heat removal from the containment to water pool is only slightly affected with value less than 3 percent.